The Effect of Workload and Work Discipline on Employee Performance at PT. Multi Mayaka in Surabaya - TARUNA, Eggi Pribadi; UTOMO, Priyo; ARIFIN, Syamsul (International Journal of Environmental, Sustainability, and Social Science, 2025)
This study aims to analyze the influence of workload and work discipline on employee performance at PT. Multi Mayaka in Surabaya. The research sample consisted of 36 respondents selected using a saturated sampling technique. Data collection was conducted using questionnaires, and the data analysis technique employed was Partial Least Squares (PLS). The results of the study indicate that workload does not have a significant influence on employee performance at PT. Multi Mayaka in Surabaya, whereas work discipline has a significant influence on employee performance at the company.